Subacute administration of crude khat (Catha edulis F.) extract induces mild to moderate nephrotoxicity in rats - Shewamene, Zewdneh (BioMed Central, 2014)
BACKGROUND: Although various studies have been conducted to shed light on the pharmacological actions of khat, little or no data are available regarding khat’s effect on the renal redox system. The aim of this study was therefore to investigate the potential of nephrotoxicity associated with khat exposure in rats. METHODS: Sprague Dawely rats were randomly assigned into eight experimental groups. Animals were treated with Tween80, gentamicin 100 mg/kg and khat at various doses (100, 200 and 400 mg/kg) alone or in combination with gentamicin for ten days. The animals were then sacrificed to obtain blood and renal tissues for subsequent analysis. Renal markers, including creatinine, blood urea nitrogen, antioxidant enzymes as well as markers for lipid peroxidation were determined using established protocols. In addition, histopathological changes were evaluated with hematoxilin and-eosin staining technique. RESULTS: Lower and moderate doses of khat did not alter the measured parameters compared to controls. By contrast, higher dose (400 mg/kg) of khat not only increased levels of serum creatinine and blood urea nitrogen (p < 0.001) but also levels of malondialdehyde (p < 0.01). Moreover, 400 mg/kg of khat significantly decreased enzymatic activities of superoxide dismutase (p < 0.01) and catalase (p < 0.001). When khat was administered with gentamicin, it was again the higher dose that significantly accentuated gentamicin-induced alterations in the renal system. CONCLUSIONS: Khat treatment at high dose is demonstrated to induce mild to moderate renal damage. Moreover, it creates synergy when combined with nephrotoxic drugs such as gentamicin.